Konstruksi Isu Dinasti Politik Jokowi dalam Tayangan Youtube Opini Tempo: Analisis Wacana Kritis - Rahman, Gymnastiar; Nurhadi, Jatmika (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2024)
Abstract: “This research aims to determine the construction of the Jokowi political dynasty issue in Opini Tempo YouTube broadcasts using Teun A. Van Dijk's Critical Discourse Analysis model in the form of analysis of text structure, cognition and social context. The approach used in this research is a qualitative approach by explaining the research data descriptively. The source of research data is Tempodotco's YouTube media video entitled